2006
DOI: 10.1209/epl/i2005-10496-0
|View full text |Cite
|
Sign up to set email alerts
|

The break-up of the vortex structure in a mesoscopic wire containing a constriction

Abstract: Within the nonlinear Ginzburg-Landau theory, we study the superconducting state in a mesoscopic wire containing a narrow constriction in the presence of a uniform magnetic field directed along the wire. If the narrow region is small enough so that no vortices can penetrate through it, curved vortices are formed, i.e. they enter at the top of the sample (the widest part) and exit near the constriction. At high magnetic fields a giant vortex is nucleated in the widest part of the wire which breaks up into a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…In the case of a mesoscopic sphere, we find that the vortex lines are naturally curved due to strong surface effects, as was recently also found in a wire with a constriction. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a mesoscopic sphere, we find that the vortex lines are naturally curved due to strong surface effects, as was recently also found in a wire with a constriction. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The regular array theoretical study of the 3D bulk superconductor with inclusions was done in the context of a modified version of the Ginzburg-Landau ͑GL͒ theory. Other studies based on the Ginzburg-Landau theory for 3D systems have been done, including shells 18 and constricted superconducting wires, 19 both in the extreme type-II limit.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the definition of giantand multivortex states becomes more complicated if the problem is extended to the third dimension, especially in more complicated sample geometries, where vortices are exposed to a complicated 3D interaction with the sample boundary. In previous work, 22 a breakup of the vortex structure in a 3D mesoscopic wire with a constriction was predicted. A giant vortex nucleated in the widest part of the wire and split into a smaller and/or individual vortices near the constriction.…”
Section: Introductionmentioning
confidence: 90%
“…There are many experimental (see for instance [1][2][3][4][5]) and theoretical (see for instance [6][7][8][9][10]) studies in threedimensional (3D) systems. For example, in [11], a superconducting wire with a constriction in the middle was investigated. It was found that, when a giant-vortex is nucleated in the widest part of the wire, it can break up into a smaller giant and/or individual vortices near the constriction.…”
Section: Introductionmentioning
confidence: 99%